PEER VICTIMIZATION IN JAY ASHER’S THIRTEEN REASONS WHY - Kurniati, Geni; Pangestika, Nindya (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2021)
Peer victimization is a common issue in literary works. This study is conducted in qualitative approach of analysis of peer victimization and how it impacted the main character through the narratives in the Thirteen Reasons Why novel. The goal of the study is to analyze how Peer Victimization impacted the main character, Hannah Baker which is described using the theory of Peer Victimization by Finkelhor (2012) and the interpersonal theory of suicide by Joiner (2005). The result of this study shows that Hannah Baker is the victim who experienced all kinds of violent behavior caused by her peers including physical violence, sexual victimization, and psychological/emotional victimization. This study also shows suicide is one of the impacts of Peer Victimization that happens in the novel resulted from the thwarted belonging and perceived burdensome that the main character felt which produce the desire for ending her life. The effects of peer victimization vary on different cases and suicide is one of the prevalent solutions chosen by the character that depicted in literary works.